Marketing of Library Resources, Services and Products: A Case Study of IIT Delhi - Khanchandani, Vanita; Hasan, Nabi (DESIDOC Journal of Library & Information Technology, 2016)
Indian Institute of Technology, Delhi is one of the premier institutes of India and was established in 1961. To cater the research and the teaching needs of the institute, Central Library, IIT Delhi is providing different resources, services and products to the faculty and the students. To maximise the usage and for increasing the importance, libraries in the present era around the world are adopting the different marketing strategies. Marketing besides providing sustainability, also helps in realising the goals of libraries.This paper provides a comprehensive overview on different marketing strategies adopted by libraries with special reference to Central Library, IIT Delhi for reaching to its users and to increase the outreach. The paper is intended to help professionals and the library users in knowing the various resources, services and products provided by the Central Library, IIT Delhi as a model to be explored and followed by other libraries and their administrators. DOI: 10.14429/djlit.36.3.9813